Pelatihan Aneka Olahan Kue Ibu-Ibu Dasawisma Kelurahan Meranti Pandak Kecamatan Rumbai Pesisir - liviawati, liviawati; putri, gusmarila eka; wardi, jeni (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2018)
In Kelurahan Meranti Pandak precisely in RW 1 and RW 13 most dasawismanya mothers work as housewives who only rely on income from their husbands. Mothers who are self-employed dasawisma only a small part who tried in the field of food sales and herbal medicine. The homeless mothers of RW 13 have received 2 cottage storefronts from 2 zakat houses for 2 groups. One group consists of 5 people. However, the cake business is now tends to die, because only one window of the cake is still operating, and even then the type of cake that sold little and not interesting. While homeless mothers in RW 1 many do not work that sometimes likes to complain about expenses that increasingly increasing day Based on that we community service team of the faculty of economics intends to provide motivation and skills improvement in creating cake for RW homemakers 1 and RW 13 Kelurahan Meranti Pandak Kecamatan Rumbai Pesisir from simple materials but have high added value. The purpose of IPTEKS for this community is to increase the interest of entrepreneurs, especially in the manufacture of cakes and can produce cakes from simple ingredients such as tofu, cassava and hankwe flour with interesting creations, which can increase the income of these mothers. Specific targets to be achieved is that housewives are more creative and innovative to beriwausaha with very cheap capital. The method used to achieve the goal is to provide enlightenment, motivate by sharing stories about the success of housewives in entrepreneurship as well as giving and practicing recipes of cakes from simple ingredients such as tofu, cassava and hankwe flour and menkreasikan processed baking so that attract consumer appetite in order to increase the sales revenue. The result of this community service is the housewife of RW 1 and RW 13 is very enthusiastic to participate in the training, it can be seen from the spirit of the mothers to keep coming from 14.00 until 17.00